صندوق النفقة كآلية لحماية حقوق الطفل المحضون بين المكاسب والنقائص - حويذق, عثمان; مجرالي, محمد لمين (جامعة الوادي University of Eloued, 2016)
إن الحق في النفقة، يعد من أهم الحقوق المالية، التي كفلتها التشريعات الداخلية والمواثيق الدولية للطفل، خاصة في حالة ما إذا كان هذا الأخير عبارة عن محضون، لذلك وعلى غرار باقي التشريعات المقارنة، فقد حاول المشرع الجزائري صَوْن وحماية هذا الحق، لهذه الفئة الضعيفة من المجتمع، ويعد صندوق النفقة المنشأ بموجب القانون رقم 15-01 والمؤرخ في 04 جانفي 2015، أحد أهم الآليات القانونية التي استحدثها المشرع الجزائري، في سبيل حماية وتكريس حق الطفل المحضون في النفقة، إلا أنه ومع ذلك، فقد تضمن هذا القانون إلى جانب المكاسب الحقوقية، التي كرسها، عدة نقائص وثغرات، تتناقض مع الهدف الذي أنشأ من أجله هذا الصندوق، وهذا ما سنحاول تسليط الضوء عليه من خلال موضوع دراستنا. Abstract The right to alimony is one of the most important financial rights guaranteed by internal legislation and international conventions for the child, especially the child in the case of Hadhana. So, like the rest of the comparative legislation, the Algerian legislature has tried to preserve and protect this right for this these vulnerable of society category. Alimony Fund established under Law No. 15-01, dated 04 January 2015 is considered one of the most important legal mechanisms introduced by the Algerian legislature, in order to protect and devote the right of child El- Mahdhoun to alimony. However, in addition to the devoted to human rights gains, the law includes a number of shortcomings and loopholes contrary to the desired objective of this fund.
Alimony Fund As A Mechanism To Protect The Right Of Child El- Mahdhoun Between Gains And Shortcomings
Keywords: النفقة – الحضانة- الحماية- قانون الأسرة- الطفل; alimony - Hadhana - protection – family law - Child